PENYULUHAN MENGENAI LITERASI KEUANGAN PADA IKATAN MAHASISWA TERENTANG - Pamela Pamela; Nurliza Nurliza (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2026)
Economic growth is supported by the community's level of financial literacy. A well-literate society is more easily able to understand and comprehend the intricacies of the financial services sector, which ultimately will optimally utilize financial products and services to improve welfare and protect themselves from potential losses due to crime in the financial sector. Individuals, including students, are required to have adequate financial literacy to be able to participate in the financial sector and have access to financial services. The purpose of community service activities is to educate the Terentang Student Association in financial literacy and support government efforts to increase the capacity of the Terentang Student Association. Financial literacy outreach activities carried out in collaboration with the Terentang Student Association have proven effective in improving participants' financial understanding, behavior, and attitudes.